Respostas
respondido por:
1
a)
f(x)=2x+3/4
2x+3/4=0
mmc=4
8x+3=0
8x=-3
x=-3/8
b)
f(x)=-x+9
-x+9=0
-x=-9
x=9
f(x)=2x+3/4
2x+3/4=0
mmc=4
8x+3=0
8x=-3
x=-3/8
b)
f(x)=-x+9
-x+9=0
-x=-9
x=9
123347:
obgd
respondido por:
2
Basta igualar a zero cada função afim.
f(x)=2x+3/4
2x+3/4=0
2x=-3/4
x=-3/4 /2
x=-3/8
A outra é ainda mais simples:
f(x)=-x+9
-x+9=0
-x=-9 .(-1)
x=9
f(x)=2x+3/4
2x+3/4=0
2x=-3/4
x=-3/4 /2
x=-3/8
A outra é ainda mais simples:
f(x)=-x+9
-x+9=0
-x=-9 .(-1)
x=9
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás